DEVELOPMENT OF THE STRATEGY OF PERSONNEL MANAGEMENT AS AN IMPOSSIBLE PART OF THE STRATEGIC PERSPECTIVE OF THE TRANSPORT INDUSTRY - SPITSINA, Anhelina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of strategic management of personnel development, as an integral part of the strategic perspective of the transport industry. The strategy is outlined as such, which determines the priorities of the complex formation of transport policy and effective state management, the main directions of development of the transport industry of Ukraine for the period up to 2030. Its goal is to create a safely functioning and efficient transport complex of Ukraine integrated into the global transport network; meeting the population’s transportation needs and improving business conditions to ensure the competitiveness and efficiency of the national economy in conditions of instability. The modern problems of the personnel development management system of the industry are studied, the specifics, negative and positive trends of this process are highlighted. The content of the concept of "strategic management of personnel development" was studied and its essential characteristics were determined. The main tasks, functions and principles of implementation of strategic management of personnel development as part of the strategic perspective of the transport industry are considered. The close relationship between the strategy of the development of the transport industry and the strategy of the development of its personnel has been proven. The relationship between the strategy of service quality and the strategy of personnel development, the strategy of innovative growth and development of the industry with the strategy of personnel development, the strategy of technical and technological development and the strategy of personnel development of the transport industry is substantiated.